Giant caloric effects close to any critical end point - Squillante, Lucas [UNESP]; Mello, Isys F. [UNESP]; Seridonio, A. C. [UNESP]; de Souza, Mariano [UNESP] (Elsevier, 2021)
The electrocaloric (EC) effect, i.e., the reversible temperature change due to adiabatic variations of the electric field, is of great interest due to its potential technological applications in refrigeration. Based on entropy arguments, we present a new framework to attain giant EC effects. Our findings are fourfold: (i) we employ the recently-proposed electric Grüneisen parameter ΓE to quantify the EC effect and discuss its advantages over the existing so-called electrocaloric strength; (ii) prediction of giant caloric effects close to any critical end point; (iii) proposal of potential key-ingredients to enhance the EC effect; (iv) demonstration of ΓE as a proper parameter to probe quantum ferroelectricity in connection with the celebrated Barrett's formula. Our findings enable us to interpret the recently-reported large EC effect at room-temperature in oxide multilayer capacitors [5], paving thus the way for new venues in the field.
Keywords: Crystal structure; Dielectric properties; Electronic materials; Ferroelectricity; Multilayers